Prophylactic eculizumab for kidney transplantation in a child with atypical hemolytic uremic syndrome due to complement factor H mutation. (14th June 2014) - Ranch, Daniel; Crowther, Barrett; Arar, Mazen; Assanasen, Chatchawin
Abstract We present a case of successful deceased‐donor kidney transplantation in a three‐yr‐old child with aHUS due to complement factor H mutation, using only prophylactic eculizumab treatment prior to transplant. She developed disease exacerbation in the immediate post‐operative period despite having therapeutic eculizumab concentrations and evidence for complete complement pathway blockade. The patient responded well to additional doses of eculizumab and has maintained excellent graft function and disease control in the first year post‐transplantation. The optimal dosing scheme for eculizumab in the perioperative period remains to be determined. More sensitive biomarkers of early disease activity are needed to improve disease monitoring. Finally, the duration of eculizumab therapy in patients with aHUS remains to be determined.